Metabolic Impacts of Oral Contraceptives A Comprehensive Review of Current Evidence - Zagórski, Karol; Skalska-Dziobek, Nina; Kozik, Mateusz; Małagocka, Weronika; Chybowska, Karolina; Orłowski , Mateusz; Naruszewicz, Maria; Midro, Aleksandra; Cetnarowski, Przemysław (Quality in Sport, 2024)
Introduction and objective: Oral hormonal contraception (COC) is a highly popular, as well as extensive group of medications. A significant impact of chronic COC therapy on parameters of lipid metabolism, carbohydrates, binding globulins, coagulation system and body weight of patients has been proven. Given the continuously increasing number of women using COC, initiating therapy at progressively younger ages it is reasonable to investigate the impact of individual medications on patients’ organisms completing knowledge with conclusions from newly conducted research, as well as the influence of new types of drugs on the studied indicators. Material and method: The literature was reviewed in the Pubmed database, GoogleScholar, the positions of the Polish gynecological society with the use of keywords. State of knowledge: The use of COC is widespread among women. According to the citied studies, over 80% of premenopausal women have declared using oral contraceptives. Typically, COCs consist of a combination of estrogen and progestin components, offering various possible combinations and dosing regimens. Despite their high efficacy in preventing pregnancy, their impact on lipid and carbohydrate metabolism, as well as consequences remains incompletely understood. Older generations of progestins, due to their similarity to testosterone, can cause negative androgenic effects, while more recent progestins are expected to be neutral. Summary: Each type of therapy is characterized by individual impact on the patients’ organism, however, the majority of progestins affect the increase of triglycerides, HDL and have ambiguous effect on LDL. COC has a limited influence on BMI, carbohydrate metabolism, coagulation system and glycemia.